2016
DOI: 10.1182/blood.v128.22.5976.5976
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pregnant Women with Acute Leukemia Treated for Life-Threatening Complications

Abstract: Background: Acute leukemia (AL) during pregnancy is a rare event. The incidence of AL in pregnancy has been reported as one in 100 000 [1]. The serious complications may be caused in these women as by pregnancy as by AL and chemotherapy. Aim: To evaluate the outcomes of pregnant women with AL admitted in ICU due to life-threatening complications before delivery. Patients (Pts) and Methods: 20 pregnant women with AL admitted in the intensive care unit (ICU) due to the life-threaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, in vitro assays demonstrated that viable Candida albicans cells induced an increase in PSP levels, suggesting its potential as a biomarker for sepsis secondary to fungal infections. In an experimental investigation by Bazhenov et al [ 60 ], PSP expression in peripheral blood mononuclear cells from 19 healthy volunteers was examined following challenges with Candida albicans lysate, lipopolysaccharide, or autologous serum. After 24 h, the supernatant PSP concentration was 59.8 pg/mL (range, 29.7–140 pg/mL) for lipopolysaccharide-treated cells, 84 pg/mL (range, 38.8–133 pg/mL) for Candida albicans lysate-treated cells, and 34.6 pg/mL (range, 18.5–81.8 pg/mL) for autologous serum-treated cells.…”
Section: Psp and Non-bacterial Infectionmentioning
confidence: 99%
“…Moreover, in vitro assays demonstrated that viable Candida albicans cells induced an increase in PSP levels, suggesting its potential as a biomarker for sepsis secondary to fungal infections. In an experimental investigation by Bazhenov et al [ 60 ], PSP expression in peripheral blood mononuclear cells from 19 healthy volunteers was examined following challenges with Candida albicans lysate, lipopolysaccharide, or autologous serum. After 24 h, the supernatant PSP concentration was 59.8 pg/mL (range, 29.7–140 pg/mL) for lipopolysaccharide-treated cells, 84 pg/mL (range, 38.8–133 pg/mL) for Candida albicans lysate-treated cells, and 34.6 pg/mL (range, 18.5–81.8 pg/mL) for autologous serum-treated cells.…”
Section: Psp and Non-bacterial Infectionmentioning
confidence: 99%